Price or Privilege? Customer Perception on Loyalty Programs - Furinto, Asnan (UI Scholars Hub, 2021)
The main purpose of the research is to understand how customers perceive loyalty programs. The author argues that types of loyalty programs could be classified into two: price based and privilege based. This research models that customer perceptions on loyalty programs, differ between these two types, and is contingent upon the relationship between customers and firm. Using settings of air-line domestic passengers and bank customers in Indonesia, the research provides evidence that price based rewards are perceived to provide higher utility perception in contractual relationships compared to non contractual relationships. However, this research failed to provide empirical support that privilege based rewards are perceived to provide higher utility perception in non contractual relation-ship compared to contractual relationship. Firms are therefore, encouraged to incorporate affective elements into their loyalty programs, on top of monetary elements, in order for the loyalty programs to be better perceived by their customers.